Arginine, glycine, aspartic acid peptide-modified paclitaxel and curcumin co-loaded liposome for the treatment of lung cancer: in vitro/vivo evaluation - Jiang K (Dove Medical Press, 2018)
Kanqiu Jiang,* Mingjing Shen,* Weihua Xu Department of Cardiothoracic Surgery, The Second Affiliated Hospital of Soochow University, Suzhou Shi, Jiangsu Sheng, People’s Republic of China *These authors contributed equally to this work Purpose: In this study, a novel arginine, glycine, aspartic acid peptide (RGD)-modified paclitaxel and curcumin co-loaded liposomes were developed to evaluate their antitumor activity in vitro and in vivo. Materials and methods: Co-loaded liposomes were prepared using the solvent evaporation method. The particles had spherical shapes under electron microscopy with sizes <130 nm. Results: By comparison with the free drug, RGD-modified paclitaxel and curcumin co-loaded liposomes and paclitaxel and curcumin co-loaded liposomes have sustained-release properties in vitro. In vivo, there was no significant difference in pharmacokinetic parameters between the RGD-modified paclitaxel and curcumin co-loaded liposomes and paclitaxel and curcumin co-loaded liposomes. A strong green fluorescence was observed in the cytoplasmic region after incubation of RGD-modified paclitaxel and curcumin co-loaded liposomes for 2 h. RGD-modified paclitaxel and curcumin co-loaded liposomes showed a superior antiproliferative effect on A549 cells with a possible mechanism that suppressed the multidrug resistance phenomenon and exhibited a clear synergistic effect. Conclusion: The results indicate that RGD-modified paclitaxel and curcumin co-loaded liposomes had a better antitumor effect in vivo than the non-modified LPs. These results indicate that RGD-modified co-loaded liposomes are a promising candidate for antitumor drug delivery. Keywords: arginine, glycine, aspartic acid peptide, paclitaxel, curcumin, liposome, cell uptake, cytotoxicity study, in vivo anti-tumor study